Epiloia: estudio multidisciplinario de un caso - Roba Izzeddin; Maria Salas-Mireles; Armida Acuña-Rodríguez (Universidad de Antioquia, 2004)
Epiloia it's a genetic disease with dominant autosomic source which presents alterations in chromosomes 9 and 16. The clinical picture is typical and laboratory findings permit to make a precise diagnosis. In the study a 27 year old with this disorder was examined, he presented epileptic seizures, mental retardation, intracranial calcification, facial angiofibromas and defects of tooth structure that include enamel pitting, inflammatory gingival enlargement hyperplasia and multiple mucosal fibromas. The diagnosis was confirmed by means of consultation with the services of Neurology, Dermatology, Dentistry and Genetics.